(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Iron deficiency anemia (IDA) is a prevalent nutritional disorder affecting a significant portion of the global population, particularly in developing countries. It is characterized by insufficient iron levels, leading to decreased red blood cell production and reduced oxygen transport capacity. This condition results in symptoms such as fatigue, weakness, and impaired cognitive function, which can substantially impact overall health and productivity. The primary causes of IDA include inadequate dietary iron intake, poor iron absorption, and chronic blood loss. Nutritional interventions, including increased consumption of iron-rich foods and fortification strategies, play a crucial role in the prevention and management of IDA. This paper reviews the relationship between nutrition and iron deficiency anemia, discussing the importance of dietary sources of iron, the impact of dietary enhancers and inhibitors on iron absorption, and the role of public health initiatives in addressing this global health challenge.